Comparative analysis of government extension services for rice farmers the case of Banaybanay and Lupon, Davao Oriental - Laureta, Rutchiel D.; Hualda, Luis Antonio T. (Davao City School of Management, University of the Philippines Mindanao, 2016)
Rice is the staple food of the Philippines which sustains the survival of the country?s mass population. Problematically, the country?s population grows 2% annually while rice production increases 1.90% at most. Accordingly, rice has become the central focus of government the national budget and food security policies. However, despite government efforts especially in conducting extension services, the country still remains to be self-sufficient. Hence, there is a need to determine the appropriateness and effectiveness of the existing extension services provided to the rice farmers especially from those main production areas like Banaybanay, and Lupon, Davao Oriental. Based on the descriptive and qualitative analysis, Banaybanay executes extension services in a more effective and efficient manner compared to Lupon. This is shown by a higher percentage of implemented quantity of programs and achieved target performance quality by the farmers and the presence of more gaps on the latter. Moreover, gaps of both municipalities lies in 3 aspects: (1) MLGU support, (2) Delivery of Services (3) Participation and Adaptation of Farmers. The researcher also found out that extension services offered are too fixated to production problems, thus overlying market oriented problems such as value adding, financing, pricing, certification, crop insurance and extra livelihood needs by which farmers strive for knowledge the most. In connection with this, recommendation were given such as provision of more LGU legal and financial counterparts; more incentives to AEWs and farmer, organizational strengthening within and among offices including farmer organizations; and a tracking system device for stringent monitoring of extension services from national to LGUs.
Thesis (BS Agribusiness Economics)-- University of the Philippines Midnanao, June 2016